Influence of several size properties on soil surface reflectance - Cierniewski, Jerzy; Kuśnierek, Krzysztof (Quaestiones Geographicae, 2010)
Several examples are provided here to quantify how the soil is influenced by the soil surface properties, i.e.: content and composition of organic matter, content of calcium carbonate, texture, moisture, as well as surface roughness. 28 soil samples were collected from the test area on a ground moraine, located north of Poznań. The soil samples were measured spectrally with an ASD FieldSpec 3 spectrophotometer in controlled laboratory conditions, in order to obtain a plot of the soil reflectance as a function of wavelength, from 400 nm to 2500 nm. The soil samples were also analyzed in the laboratory to establish their selected properties. The research shows that all tested soil properties strongly influence the soil reflectance.